Role of Ahmet Davutoğlu in Turkish foreign policy - Assistant Professor Dr. Emad Razik Omar; Assistant Lecturer Mohamed Nour Hussein Abd (The college of law and political science journal, 2023)
The arrival of the Justice and Development Party in 2002 constituted a new case in Turkish foreign policy, as it gave a fundamental shift in the way Turkey deals with the issues that are the focus of its attention.  It moved towards pragmatic policies based on zeroing problems and maximising the gains that can be obtained. Turkey's position and importance helped in giving it a new role, and accordingly it is also aware of the strengths in its foreign policy, and one of the most important factors that helped is the presence of political elites such as Ahmed Daoud  Davutoglu, who held several positions and who was able through his vision known as neo-Ottomanism to enhance Turkey’s position in Europe, Asia and Africa and to take Turkish political behavior to participation and effectiveness in a way that was not entrusted to him before. Ahmed Davutoglu wanted to take advantage of Turkey’s advantages as much as possible and that  He stays away from the factors that would weaken Turkey's regional role.